Efektivitas Persepsi Kegunaan dan Tagline “15 Menit Sampai” terhadap Keputusan Pembelian Layanan Astro E-grocery - Felisia Titania; Moehammad Gafar Yoedtadi (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2026)
This study analyzes how perceived usefulness and the quality of the “15-minute delivery” advertising message influence consumers’ purchasing decisions on purchase decisions for essential goods through the Astro e-grocery application. The rapid growth of e-grocery services and increasing competition in quick commerce emphasize the necessity of evaluating advertising message effectiveness and consumer perceptions regarding dgital shopping advantages. This research applies Davis’s Perceived Usefulness framework, the AIDA model for advertising message quality, and Kotler and Armstrong’s theory of consumer purchase decisions. Using multiple regression as the main analytical method, the study meets all classical assumption requirements, including normality, absence of multicollinearity, and heteroscedasticity. The result reveal that perceived usefulness and advertising message quality exert both simultaneous and partial significant effects on consumer purchasing decisions, demonstrating that the combination of practical service benefits and compelling message delivery enhances user confidence and decision-making efficiency. These findings emphasize that effective message delivery combined with meaningful functional value plays a crucial role in driving consumer purchasing decisions. Overall, the study offers strategic insights for digital marketing communication in the e-grocery sector, particularly in optimizing message relevance and strengthening consumer perceptions within the increasingly competitive e-commerce. Penelitian ini bertujuan untuk menganalisis pengaruh Persepsi Kegunaan dan Kualitas Pesan Iklan “15 Menit Sampai” terhadap keputusan pembelian kebutuhan konsumen pada aplikasi Astro e-grocery. Pesatnya perkembangan e-grocery serta persaingan salaquick commerce mendorong pentingnya analisis efektivitas pesan iklan dan persepsi konsumen terhadap manfaat layanan belanja digital. Penelitian ini menggunakan teori persepsi kegunaan dari Davis, model kualitas pesan iklan AIDA, dan teori keputusan pembelian dari Kotler dan Armstrong. Melalui analisis regresi berganda, prosedur pengujian asumsi klasik menunjukkan terpenuhinya kriteria normalitas, bebas multikolinearitas, dan heteroskedastisitas. Hasil penelitian menunjukkan bahwa persepsi kegunaan dan kualitas pesan iklan memberikan dampak dengan pengaruh simultan dan parsial yang signifikan, membantu konsumen memperoleh pengalaman berbelanja e-grocery yang lebih praktis. Temuan ini menyatakan bahwa persepsi kgunaan dan Kualitas Pesan Iklan memberikan dampak positif yang signifikan, penting dalam mendorong perilaku pembelian konsumen pada platform Astro e-grocery dan memberikan kontribusi strategis bagi komunikasi pemasaran digital di sektor e-grocery.